Training on Management of Tourism Potential and UMKM in Nagrog Tonjong Canyon Village Using Social Media - Media Aditia Abdurachman1; Rizky Ridwan2; Alfin Nur Arifah; Dheri Febiyani Lestari; Ramdani Al Falah; Aldy Agustian (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Nagrog Village possesses untapped tourism potential, particularly at the Tonjong Canyon site. The primary challenges include inadequate infrastructure, limited community involvement in tourism management, and minimal social media promotion. The community service methods applied in this activity include field observation, planning, and training of local residents in tourism management and social media. The results show increased community awareness of tourism potential, infrastructure improvements, and enhanced promotion through social media. This initiative has contributed to increasing visitor numbers and the village's economy by leveraging its tourism assets